Anne Carter and Input-Output: Technology, Trade, and Pollution - Thijs ten Raa; William J. Baumol (Œconomia, 2011)
We pay tribute to Anne Carter’s contributions to economic analysis. Mainstream economic models, including input-output studies, consider technology as given and do not question the co-existence of different national economic techniques. Carter, however, addresses this key question. Her book, Structural Change in the American Economy (1970), was well ahead of its time. The techniques Carter compared were differentiated by time, but the comparative analysis is equally applicable to a comparison of techniques that are differentiated by location, such as those of the EU-15 member states. We apply Carter’s method for the determination of the optimal choice of technique to the problem of allocating production among different countries, so as to make use of their comparative advantages in producing commodities and in meeting environmental constraints. We also draw attention to Carter’s recent work on ever deeper questions regarding variations in technology.